2010
DOI: 10.1177/156482651003100222
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infant and Young Child Feeding Practices in Nepal: Secondary Data Analysis of Demographic and Health Survey 2006

Abstract: Most breastfeeding indicators in Nepal are below the expected levels to achieve a substantial reduction in child mortality. Breastfeeding promotion strategies should specifically target mothers who have more contact with the health care delivery system, while programs targeting the entire community should be continued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
64
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 4 publications
17
64
4
1
Order By: Relevance
“…Our results indicated that infant and young child feeding practices in the South Asia region have not reached the expected levels that are required to achieve a substantial reduction in child a. The adjusted odds ratios for these factors from the multiple logistic regression models can be found in table 5 in the papers in this Special Section from Bangladesh [17], India [18], and Nepal [19] and in table 4 in the paper from Sri Lanka [20]. b.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Our results indicated that infant and young child feeding practices in the South Asia region have not reached the expected levels that are required to achieve a substantial reduction in child a. The adjusted odds ratios for these factors from the multiple logistic regression models can be found in table 5 in the papers in this Special Section from Bangladesh [17], India [18], and Nepal [19] and in table 4 in the paper from Sri Lanka [20]. b.…”
Section: Discussionmentioning
confidence: 73%
“…a. The adjusted odds ratios for these factors from the multiple logistic regression models can be found in table 5 in the papers in this Special Section from Bangladesh [17], India [18], Nepal [19], and Sri Lanka [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some common factors such as changing lifestyles, aggressive promotion of formula milk, a general unawareness of the importance of breast-feeding and perceived insufficiency of milk could play important roles in contributing towards suboptimal feeding practices. In women delivered through Caesarean section there is a perceived insufficiency of milk contributing towards high bottle-feeding rate, which is a common finding in India, Nepal, Sri Lanka and China where it was the main reason for delayed contact (21,(34)(35)(36) . This perceived insufficiency was also found to be the most common cause for discontinuing breast-feeding of children in Australia (37) .…”
Section: Discussionmentioning
confidence: 99%
“…This study has found that demographic determinants such as age of mother, level of education, age and gender of child, family type and size were found to be associated significantly with nutritional problems in 3-5 years old children of Kaski district [51], [59]. present study revealed that majority of respondents (57%) had more…”
Section: Discussionmentioning
confidence: 48%